Looking beyond the COVID-19 Pandemic: Congregants’ Expectations of Future Online Religious Service Attendance - Jacobi, Christopher Justin (Religions, 2022)
Many religious congregations in the United States have adapted to COVID-19 lockdowns by offering religious services online. This study aims to understand whether congregants from a diverse set of faith traditions expect to attend online or in-person religious services after the pandemic. First, it examines how members of different religious traditions vary in their expectations of future attendance. Second, it explores whether respondents’ habituation to online attendance during the pandemic might result in greater preference for future online attendance. This study draws on a non-representative sample of 1609 members of Christian, Jewish, and Hindu communities in four US states surveyed in late 2020 and employs logistic regression models. The findings first suggest a divergence between congregation types that require in-person attendance for certain rituals versus those that do not. Second, habituation of the practice of online attendance may cultivate the desire to sustain this practice into the future. Online religious services have been well received by most congregants, and online services will likely play a useful role across congregation types, albeit at differing levels and with different audiences. Our finding that marginal congregants were more likely to prefer online religious services, while more engaged members preferred in-person attendance, is of relevance to faith leaders.